Preventiva in zdravljenje patelofemoralne bolečine - Kržičnik, Zala (Šport (Ljubljana), 2022)
Patellofemoral pain is defined as pain in the anterior part of the knee, in the region between patella and femur. The knowledge of this injury is important, as it is one of the most common musculoskeletal injuries affecting young and active adults. In this article, we performed an umbrella review of the existing systematic reviews and meta-analyses to determine the most effective treatments for this pain syndrome. The results of the literature review suggest that hip and knee-strengthening exercises are the ultimate for prevention and improvement of the syndrome. The evidence on the effectiveness of other conservative treatment methods is scarce. Based on our review of the literature, we found that the prevention and treatment of patellofemoral pain are supported by limited evidence, and further research would be needed to explore these topics further.
Keywords: analize; kolenski sklep; patelofemoralna bolečina; preventivni program; šport; športne poškodbe; vadba; zdravljenje